2017
DOI: 10.4103/0019-5413.201704
|View full text |Cite
|
Sign up to set email alerts
|

Complication rate during multilevel lumbar fusion in patients above 60 years

Abstract: Background:Spine surgery in elderly with comorbidities is reported to have higher complication rates and increased cost. However, the surgical outcome is good irrespective of the complications. Hence, it is essential to identify the factors affecting the complication rates in such patients and the measures to reduce them. This retrospective observational study determines the perioperative complications, their incidence and the measures to reduce complications in the elderly with comorbidities, operated by inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…In line with previous findings, the reported risk factors of PLIF such as fixation of multiple levels, longer operations, and non-union have shown a positive link between these factors and complication rates [ 45 ]. Continuous bleeding from the operation site while proceeding at other levels was one reason for the increased rate of complications associated with longer surgeries [ 45 ]. In aspects of cage placement, smaller cages increase the likelihood of posterior cage migration, which was also corroborated by previous findings.…”
Section: Discussionsupporting
confidence: 86%
“…In line with previous findings, the reported risk factors of PLIF such as fixation of multiple levels, longer operations, and non-union have shown a positive link between these factors and complication rates [ 45 ]. Continuous bleeding from the operation site while proceeding at other levels was one reason for the increased rate of complications associated with longer surgeries [ 45 ]. In aspects of cage placement, smaller cages increase the likelihood of posterior cage migration, which was also corroborated by previous findings.…”
Section: Discussionsupporting
confidence: 86%
“…Vijay et al determined that lower vitamin D level played an important role in a lower rate of and a longer time to fusion. [ 29 , 30 ] In our study, we also found that serum vitamin D (OR = 0.79, P < .001) was significant predictor of nonunion. These findings indicate it is necessary to proceed a prospective study to analyze the role of vitamin D supplementation on spinal fusion.…”
Section: Discussionsupporting
confidence: 73%
“…The complication rate is higher following multilevel fusion due to longer operative time, more intraoperative blood loss and requirement for additional bone graft, especially in older patients [13]. There were no intraoperative or postoperative complications in our study where the patients ranged in age from 16 to 69 years.…”
Section: Discussionmentioning
confidence: 57%